2002
DOI: 10.1046/j.1460-2687.2002.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

The curve kick of a football I: impact with the foot

Abstract: The purpose of this study is to assess the fundamental characteristics which cause a football to spin in a curve ball kick. The ball impact process was analysed initially with a high speed video camera running at 4500 frames per second to obtain the basic data for a computer simulation model. This simulation model showed suitable agreement although it slightly deteriorated during the latter half of impact. It was noted that rotation of the ball occurs, even if the kinetic coefficient of friction is nearly equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 9 publications
5
57
1
2
Order By: Relevance
“…From observation, the critical impact and high stress was located at the metatarsal region of the upper foot area. It can proved the research done by Asai et al (2002), which is instep kicking will affected to the metatarsal region. When changing boots, it is actually change the material and thickness as well.…”
Section: S662mentioning
confidence: 79%
“…From observation, the critical impact and high stress was located at the metatarsal region of the upper foot area. It can proved the research done by Asai et al (2002), which is instep kicking will affected to the metatarsal region. When changing boots, it is actually change the material and thickness as well.…”
Section: S662mentioning
confidence: 79%
“…Such a movement consequence observed in the present study, as participants were able to better flex their knee during the backswing movement (pre-support phase) and afterwards to be able to have a more extended knee in order to perform more powerful kicks. The lower ankle plantar flexion after fatigue had also an effect on the quality of foot-to-ball contact causing impairments in the final velocity imparted to the ball (18)(19)(20). Asami and Nolte (20) reported that better performance (faster kick) is achieved when the contact point is located closer to the ankle rather than the metatarsals.…”
Section: Discussionmentioning
confidence: 99%
“…Launch condition data adapted from Asai et al [9]. Understanding the effect of seams on the aerodynamics of an association football M J Carré *, S R Goodwill and S J Haake Football, Re = 1.7e5…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by using a three-dimensional trajectory simulation model that calculated the forces experienced by the ball at discrete time intervals during its flight using the equations 1 and 2 (a time step of 2.5 ms was used). The coefficients C d and C m According to the Asai et al [9] data in Table 1 If the foot impact location was off-set by 80 mm to the right (see Table 1 the same throughout and the Magnus coefficient also remained fairly constant due to the combined effect of reducing Reynolds number and increasing spin parameter. For this simulation, the value of spin was assumed to stay constant throughout.…”
Section: Kick Simulationsmentioning
confidence: 99%